RANCANGAN USULAN PERBAIKAN PADA ALUR PROSES DAN FORMULIR PCR (PROCESS CHANGE REQUEST) DI PT. XYZ - Ken Warsy Triastuti; Sutrisno Sutrisno (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2021)
PT. XYZ is an automotive manufacturing industry. In productivity, PT. XYZ supplied the products of several suppliers. Therefore, it requires a measure of quality assurance for suppliers and supply items so that PT. XYZ may obtain more items according to the established standards. Process Change Request (PCR) is the application for standard supply change on components such as 4M (Man, Machine, Method, Material). The process grooves and PCR forms are standardized and listed on the SQAM (Supplier Quality Manual Assurance). Supplier Quality Assurance Manual (SQAM) is associated with ISO 9001 about its quality management and process systems. The flow of processes and PCR forms has been found a problem of misalignment between the ideal time and the actual time of implementation of the PCR phase, which has slowed down the supply of PT. XYZ. In the study a plan to improve the process flow and PCR forms by applying the kaizen concept approach (continuous improvement) using PDCA (Plan-Do-Check-Action) methods step plan and fishbone diagram.